(3JMQje PHGFM Cgd GdcJGHs - (3GdYGedj, HgGA GdOjf, HgGA GdOjf GdYGedj, eMeO Hf MSjf Hf YHO GdUeO, J (B1031(3g` (B1622(3es ((3GdeTgO GdZQhejs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg Ydi LRjd CaVGdg (B... (3Ef GdHGYK Ydi JCdja gPg GdebGdI hJMQjQ gPg GdQSGdI Cf QShd edc GdQhe deG hQO HGdQSGdI Edi gPg GdHdGO PcQ aj HYV GdCjGf Cf CYXe eG jTfY Hg YdeGA GdQhe Ydi YdeGFce (B... (3Mcece HJMQje PHGFM Cgd GdcJGHs
(3BNQgG (B:s
(3BNQgG(B: (3hdhdG Cf bhdg gPG bhd fGOQ eNGda ddTgQI hddQhGjGJ GdeTghQI GdeJWGaQI GdeYJVOI HYed LeGgjQ YdeGFfG GdeMehdI YfOge Ydi EWdGbgG dcGf GdYed Hg ZjQ HYjO Yf GdUhGH hHg jMUd GdLeY Hjf GdQhGjGJ GdeJNGdaI aj gPG GdHGH ef Ohf MGLI Edi Med TjA efgG Ydi GdJbjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 102s
(3GdPQjYI, L (B10: 5s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis